An Open Source-Based BCI Application for Virtual World Tour and Its Usability Evaluation - Woo, Sanghum; Lee, Jongmin; Kim, Hyunji; Chun, Sungwoo; Lee, Daehyung; Gwon, Daeun; Ahn, Minkyu (Frontiers in Human Neuroscience, 2021)
A brain computer interfaces (BCIs) can provide a new communication channel and control functions to people with restricted movements. Recent studies have indicated the effectiveness of BCI applications. Various types of applications have been introduced so far in this field, but the number of those available to the public is still insufficient. Thus, there is a need to expand the usability and accessibility of BCI applications. In this study, we introduce a BCI application for users to experience a virtual world tour. This software was built on three open source environments and is publicly available through the GitHub repository. For a usability test, 10 healthy subjects participated in an electroencephalography (EEG) experiment and evaluated the system through a questionnaire. As a result, all participants successfully played the BCI application with 96.6% accuracy with 20 blinks from two sessions and gave opinions on its usability (e.g., controllability, completeness, comfort, and enjoyment) through the questionnaire. We believe that this open-source BCI world tour system can be used in both research and entertainment settings and hopefully contribute to open science in BCI field.